Heteroatoms Synergistic Anchoring Vacancies in Phosphorus-Doped CoSe2 Enable Ultrahigh Activity and Stability in Li–S Batteries - Zhou, Xiaoya; Mao, Wei; Ye, Chengwei; Liang, Qi; Wang, Peng; Wang, Xuebin; Tang, Shaochun (Nano-Micro Letters, 2025)
Electrocatalyst activity and stability demonstrate a “seesaw” relationship. Introducing vacancies (Vo) enhances the activity by improving reactant affinity and increasing accessible active sites. However, deficient or excessive Vo reduces polysulfide adsorption and lowers catalytic stability. Herein, a novel “heteroatoms synergistic anchoring vacancies” strategy is proposed to address the trade-off between high activity and stability. Phosphorus-doped CoSe2 with remained rich selenium vacancies (P-CS-Vo-0.5) was synthesized by producing abundant selenium Vo followed by controlled P atom doping. Atomic-scale microstructure analysis elucidated a dynamic process of surface vacancy generation and the subsequent partial occupation of these vacancies by P atoms. Density functional theory simulations and in situ Raman tests revealed that the Se vacancies provide highly active catalytic sites, accelerating polysulfide conversion, while P incorporation effectively reduces the surface energy of Se vacancies and suppresses their inward migration, enhancing structural robustness. The battery with the optimal P-CS-Vo-0.5 separator delivers an initial discharge capacity of 1306.7 mAh g−1 at 0.2C, and maintain 5.04 mAh cm−2 at a high sulfur loading (5.7 mg cm−2, 5.0 μL mg−1), achieving 95.1% capacity retention after 80 cycles. This strategy of modifying local atomic environments offers a new route to designing highly active and stable catalysts. Highlights: 1 A volcano-type relationship between catalytic activity and vacancy concentration is revealed based on systematic investigation on selenium-vacancy-rich CoSe2. 2 A novel “heteroatoms synergistic anchoring vacancies” tactic is firstly proposed to achieve P-doped CoSe2 with remained rich selenium vacancies (P-CS-Vo-0.5). 3 It has been demonstrated that P doping lowers Se vacancy surface energy and effectively “pins” active sites, markedly suppressing dynamic migration of vacancies.